2020
DOI: 10.1186/s12944-020-01264-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal serum HDL-c concentrations during pregnancy and neonatal birth weight: a population-based cohort study

Abstract: Background: To evaluate the associations between maternal serum concentrations of high-density lipoprotein cholesterol (HDL-c) throughout pregnancy and neonatal birth weight (BW) and small for gestational age (SGA) births. Methods: A prospective cohort of 2241 pregnant women was followed from recruitment to delivery in three hospitals in Beijing, China between January 2014 and December 2017. Maternal fasting serum lipids concentrations were measured at gestational week 6-12, 16, 24 and 36. Major outcome was ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…While previous studies did not propose any association between maternal LDL-c levels and abnormal birth weight ( 44 46 ), we observed elevated LDL-c in the first trimester increased odds of LGA, but not macrosomia. In the current study, no detectable association between maternal HDL-c and birth weight or adverse birth outcomes was found as previously suggested in several studies ( 47 , 48 ) ( 36 , 49 ). The inconsistent results in different studies could be explained by different gestational weeks when the blood was collected and the variances in the study population.…”
Section: Discussionsupporting
confidence: 85%
“…While previous studies did not propose any association between maternal LDL-c levels and abnormal birth weight ( 44 46 ), we observed elevated LDL-c in the first trimester increased odds of LGA, but not macrosomia. In the current study, no detectable association between maternal HDL-c and birth weight or adverse birth outcomes was found as previously suggested in several studies ( 47 , 48 ) ( 36 , 49 ). The inconsistent results in different studies could be explained by different gestational weeks when the blood was collected and the variances in the study population.…”
Section: Discussionsupporting
confidence: 85%
“…Jin et al 25 found that the high third-trimester TG concentration was associated with a decreased risk for SGA and an increased risk for LGA. Di Cianni et al 28 and a recent Dutch study 14 also found similar results in different gestational ages. In recent years, studies have found that elevated TG levels lead to vascular endothelial dysfunction and enhanced lipid peroxidation which resulted in damage to vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 55%
“…Misra et al 27 also reported a negative association between HDL-C and birth weight at all time points starting at 10 weeks’ gestation in overweight or obese women. One recent study 28 showed that maternal serum HDL-C concentrations were inversely associated with birthweight at 24th and 36th gestational weeks and the high concentrations of HDL-C at the 36th gestational week increased the risk of SGA. There was a tendency that pregnant women with higher HDL-C concentrations throughout pregnancy gave birth to infants with lower birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review found that the risk of PTB was not affected by HDL-c [21]. There was also a tendency for maternal high levels of HDL-c to be associated with an increased risk of SGA [22][23][24]. Therefore, controversies still exist regarding the correlation between maternal HDL-c and PTB and SGA.…”
Section: Introductionmentioning
confidence: 99%